A novel approach to studying infective endocarditis: Ultrasound-guided wire injury and bacterial challenge in mice - Benedikt Bartsch; Ansgar Ackerschott; Muntadher Al Zaidi; Raul Nicolas Jamin; Mariam Louis Fathy Nazir; Moritz Altrogge; Lars Fester; Jessica Lambertz; Mark Coburn; Georg Nickenig; Marijo Parcina; Sebastian Zimmer; et al. (PLoS ONE, 2025)
Background Infective endocarditis (IE) is frequently caused by Staphylococcus aureus (S. aureus) and most commonly affects the aortic valve. Early diagnosis and treatment initiation are challenging because the involved immunological processes are poorly understood due to a lack of suitable in vivo models. Objectives To establish a novel reproducible murine IE model, based on ultrasound-guided wire injury (WI) induced endothelial damage. Methods IE was established by inducing endothelial damage via ultrasound-guided wire injury followed by bacterial challenge with S. aureus using 10 4-6 colony-forming units (CFU) 24h to 72h after wire injury. Cross-sections of valvular leaflets were prepared for scanning electron microscopy (SEM) and immunofluorescence microscopy to visualize valvular invasion of macrophages, neutrophils, and S. aureus. Bacterial cultivation was carried out from blood and valve samples. Systemic immune response was assessed using flow cytometry. Results Wire injury induced endothelial damage was observed in all mice after wire-injury in SEM imaging. We reliably induced IE using 10 5 (85%) and 10 6 (91%) CFU S. aureus after wire injury. Aortic regurgitation was more prevalent in wire injury mice after bacterial challenge. Mice undergoing bacterial challenge responded with significant neutrophilia and elevated pro-inflammatory cytokines in the blood. Immunofluorescence staining revealed significantly increased immune cell accumulations using our proposed model compared to controls. Conclusion Echocardiography and ex vivo histological staining demonstrated consistent infective endocarditis induction in our new model, combining a wire injury-induced endothelial damage and S. aureus administration. Further exploration of the initial immune cell response and biomarker expression could potentially identify indicators for early IE diagnosis and novel treatment targets.